2020
DOI: 10.1038/s41598-020-64980-8
|View full text |Cite
|
Sign up to set email alerts
|

A novel predicted model for hypertension based on a large cross-sectional study

Abstract: Hypertension is a global public health issue and leading risk for death and disability. It is urgent to search novel methods predicting hypertension. Herein, we chose 73158 samples of physical examiners in central China from June 2008 to June 2018. After strict exclusion processes, 33570 participants with hypertension and 35410 healthy controls were included. We randomly chose 70% samples as the train set and the remaining 30% as the test set. Clinical parameters including age, gender, height, weight, body mas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 53 publications
2
14
0
Order By: Relevance
“…Two studies mentioned above were carried out either in a single rural area or urban area. Another predicted model for hypertension based on a large cross-sectional study was established recently ( Ren et al, 2020 ). In spite of a large group of people (73,158 samples), the prediction performances of the model were simply assessed by probability of disease (POD) index and AUC values (76.52% in the train set and 75.81% in the test set).…”
Section: Discussionmentioning
confidence: 99%
“…Two studies mentioned above were carried out either in a single rural area or urban area. Another predicted model for hypertension based on a large cross-sectional study was established recently ( Ren et al, 2020 ). In spite of a large group of people (73,158 samples), the prediction performances of the model were simply assessed by probability of disease (POD) index and AUC values (76.52% in the train set and 75.81% in the test set).…”
Section: Discussionmentioning
confidence: 99%
“…An increase in UA implies an increased risk of future cardiovascular disease [21,45] . In a cross-sectional study of 33,570 patients with HBP by Ren et al, the established risk-prediction model included variables such as Gender, Age, Height, Weight, and UA [17] . Meanwhile, Rosa et al proposed that UA is an important NAFLD predictor variable [46] .…”
Section: Model Evaluation and Comparisonmentioning
confidence: 99%
“…This study also found that SBP was one of the main predictors of concurrent HBP and NAFLD, and there is a correlation between BMI and HBP [34,35] . The results of an HBP prediction model study based on 135,715 individuals showed that a lower BMI reduced the risk of developing HBP [17] . Among patients with HBP in the United States, 49.5% are obese (BMI > 28) [36] .…”
Section: Model Evaluation and Comparisonmentioning
confidence: 99%
See 1 more Smart Citation
“…interaction between risk factors, which were mainly carried out in the general population, and there were few relevant studies in people who were Overweight and obesity. Recently, Ren Z [29] and others have discussed the prediction model and independent risk factors of hypertension in Central China. Chen y [30] and others analyzed the population in northern China and constructed the corresponding hypertension prediction model.…”
Section: Limitationsmentioning
confidence: 99%